Albumin-assembled copper-bismuth bimetallic sulfide bioactive nanosphere as an amplifier of oxidative stress for enhanced radio-chemodynamic combination therapy. (5th July 2022) - Tao, Weiyong; Tuo, Zhan; Wu, Feige; Mu, Ketao; Xu, Cunjing; Shi, Yuxiao; Sun, Zeyu; Wang, Yifan; Li, Yan; Zhong, Zhenyu; Zhou, Lei; Wang, Jianglin; et al.
Abstract: The tumor microenvironment with overexpressed hydrogen peroxide (H2 O2 ) and reinforced antioxidative system (glutathione, GSH) becomes a double-edged sword for the accessibility of nano-therapy. Since reactive oxygen species (ROS) are easily quenched by the developed antioxidative network, ROS-based treatments such as chemodynamic therapy (CDT) and radiotherapy (RT) for killing cancer cells are severely attenuated. To overcome such limitations, a bioactive nanosphere system is developed to regulate intracellular oxidative stress for enhanced radio-chemodynamic combination therapy by using bovine serum albumin (BSA) based bioactive nanospheres that are BSA assembled with in situ generated copper-bismuth sulfide nanodots and diallyl trisulfide (DATS). The copper-bismuth sulfide nanodots react with H2 O2 to produce OH and release Cu 2+ . Then, the Cu 2+ further depletes GSH to generate Cu + for more OH generation in the way of Fenton-like reaction. Such a cascade reaction can initiate OH generation and GSH consumption to realize CDT. The elevation of ROS triggered by the DATS from BBCD nanospheres further augments the breaking of redox balance for the increased oxidative stress in 4T1 cells. With the sensitization of increased oxidative stress and high Z element Bi, an enhanced radio-chemodynamic combination therapy is achieved. The current work provides an enhanced radio-chemodynamic combination treatment for the majority of solid tumors by using the co-assembled bioactive nanospheres as an amplifier of oxidative stress. Graphical Abstract: